MANAJEMEN KOMUNIKASI ORGANISASI DALAM PENGEMBANGAN KEPEMIMPINAN INSTITUT AGAMA ISLAM AL AZIZIYAH SAMALANGA BIREUEN - SABRIN . (JURNAL ILMIAH KOHESI, 2020)
This study aims to determine the communication management organization in the development of leadership Islamic Isnstitut in Al-Aziziyah Samalanga Bireuen. 4 (four) sub-question is how the communication planning organization, how the organization of organizational communication, how the implementation of organizational communication, and how to control communication organizations in the development of Islamic Institute in Al-Aziziyah Samalanga Bireuen.Theoretical framework used is organizational communication, leadership in organizational communication, organizational development, process management in communication activities, and communications management concepts of Islam. Organizational communication models according to Hunt, Cutlip, Center and Broom.This study used a qualitative approach through case study model design. Data collecting technique is done by: (1) interview, (2) participant observation, (3) study the documentation, and (4) the reference search. The informant was taken with purposive sampling techniques and then combined with snowball sampling. Data is processed using the model of Miles and Huberman, through three steps, the first to perform data reduction, both present data, and the third withdrawal or verification conclusion.The survey results revealed that the communication planning organizations in the development of Institute of Islamic Al-Aziziyah Samalanga Bireuen taking into account the development objectives, identify all the opportunities and constraints, develop a plan or a series of activities in achieving goals. Organizing communication organizations in the development of Islamic Institute in Al-Aziziyah Samalanga Bireuen in organizational communication, namely the distribution of granularity and the entire task or work to be performed every employee Islamic Institute in Al-Aziziyah Samalanga Bireuen in achieving organizational goals. The implementation of organizational communication in the development of Islamic Institute in Al-Aziziyah Samalanga Bireuen in communications made at the organization's general objectives and common strategies. In general, development goals can be explained to give instructions on how to allocate some resources and personnel available to implement the program. The development strategy related to how businesses manage some resources available to improve the quality of the Institute of Islamic Al-Aziziyah Samalanga Bireuen. Supervision of organizational communication in the development of Islamic Institute in Al-Aziziyah Samalanga Bireuen in organizational communication done that preliminary supervision, supervision conducted in conjunction with the implementation of activities and monitoring feedback, measure the result of an activity that has been completed.